Effectiveness of a Brief Point of Care Ultrasound Course at a National Nephrology Conference - Abhilash Koratala; Nilam Soni; Rupal Mehta; Nathaniel Reisinger (CINQUILL Medical Publishers Inc., 2024)
The rising demand for point of care ultrasound (POCUS) instruction during fellowship has been limited due to a shortage of trained faculty and courses designed specifically for . A hands-on POCUS was organized during the April 2023 National Kidney Foundation (NKF) Spring Clinical Meeting to address this challenge. The course consisted of lectures and a 4-hour hands-on workshop guided by multidisciplinary POCUS experts. The anonymous post-course survey received responses from 25 out of 39 participants, yielding a 64.1% response rate. On a scale of 0-10, confidence levels for acquiring kidney images rose from 2.6 + 2.3 (mean + SD) to 7.8 + 1.5 post-workshop (p<0.001). Similarly, a remarkable improvement in confidence for acquiring lung and cardiac images was seen as scores increased from 1.8 + 2.4 to 7.7 + 1.5 (p<0.001) and from 1.5 + 2.2 to 7.2 + 1.3 (p<0.001), respectively. Additionally, respondents reported a substantial improvement in their confidence to interpret kidney, lung, and cardiac POCUS images, with scores increasing from 4.5 + 2.2 to 7.7 + 1.1 (p<0.001), 2.3 + 2.4 to 7.6 + 1.5 (p<0.001), and 2 + 2 to 7.3 + 1.5 (p<0.001), respectively. Barriers to implementing POCUS use at institutions included a perceived lack of trained faculty, limited protected time for faculty, and insufficient support from division leadership. The NKF POCUS successfully improved participants' confidence in acquiring and interpreting basic POCUS images.